Morphological maturity of the knobbed spider crab, Leurocyclus tuberculosus (H. Milne Edwards & Lucas, 1842) (Brachyura, Majidae) in the Northern Patagonian Gulfs - Baron, Pedro Jose (2009)
Sexual maturation in brachyurans has three different components: physiological, morphological, and functional. The second is visualized by examining changes in the morphometric relationships between some dimensions of the organs involved in mating and egg incubation, relative to a standard measure of size. Aiming to establish the size at morphological maturity for the Patagonian knobbed spider crab, Leurocyclus tuberculosus, a morphometric analysis was conducted on specimens sampled in the northern Patagonian gulfs (41°-43°S). Discontinuities were detected in ln transformed relationships of abdomen width on carapace width of females, and right chela length on carapace width of males. For females, estimated CWmorph50% (carapace width at which 50% of the individuals attains morphometric maturity) was 47.9 mm, and CW of the smallest ovigerous female observed in the samples was 42.7 mm. For males, a change in the growth rate of ln(ChL) relative to ln(CW) was detected at 48.9 mm CW.